Alabama moon - Key, Watt. (New York : Farrar Straus Giroux, 2006)
After the death of his father, ten-year-old Moon leaves their forest shelter home and is sent to an Alabama institution, becoming entangled in the outside world he has never known and making good friends, a relentless enemy, and finally a new life.
A novel.
720
Accelerated Reader AR
Maine Student Book Award list 2007-2008.
Keywords: Orphans -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Bullying -- Fiction; Government, Resistance to -- Juvenile fiction; Alabama -- Juvenile fiction